Qingrehuoxue formula enhances anti-PD-1 immunotherapy in NSCLC by remodeling the tumor immune microenvironment via TREM2 signaling - Bin-bin Li; Yi-yang Jiang; Xue Li; Min-min Yu; Qian Meng; Dan-ni Wang; Ji-miao Zang; Fei Xu (BMC Complementary Medicine and Therapies)
Abstract Objective This study evaluated the anti-cancer effect of the Qingrehuoxue Formula (QRHXF) and explored its synergistic mechanisms with anti-programmed cell death protein 1 (anti-PD-1), focusing on the tumor mircroenvironment (TME) in non-small cell lung cancer (NSCLC). Methods The major components of QRHXF were quantified using mass spectrometry. Subcutaneous tumor mice models of Lewis lung carcinoma (LLC) were established. Mice were divided into five groups identified for pharmacodynamics: model, QRHXF (low-dose and high-dose), anti-PD-1, and anti-PD-1 + QRHXF. Tumor pathology was assessed using hematoxylin and eosin staining. Inflammatory factors were evaluated via ELISA and q-PCR. Flow cytometry was employed to quantify tumor-infiltrating immune cells. Immunofluorescence staining and western blotting (WB) were used to assess tumor angiogenesis and metastasis and confirm molecular targets and pathways. Results Animal experiments showed that QRHXF inhibited subcutaneous tumor growth in NSCLC, with the combined therapy of QRHXF and anti-PD-1 showing superior efficacy. Particularly, QRHXF reduced extracellular matrix deposition and tumor angiogenesis to inhibit tumor metastasis. Furthermore, QRHXF downregulated tumor-infiltrating M2 macrophages and enhanced T-cell cytokine activity, upregulating the antitumor immune response. The combination of QRHXF and anti-PD-1 could augment the effects of immunotherapy. Mechanistically, QRHXF exerted its antitumor activity by inhibiting targeting triggering receptor expressed on myeloid cells 2 (TREM2) and PI3K/AKT/STAT6 pathways. Conclusion QRHXF enhanced antitumor immune responses in NSCLC via TREM2 and modulation of the PI3K/AKT/STAT6 signaling pathway, reducing chemotactic infiltration of M2 tumor-associated macrophages within the TME. This suggests its potential as an adjuvant immune therapy for improved patient outcomes.